Diversity of scale insects (Hemiptera, Coccomorpha) in ten varieties of olive trees (Olea europaea L.) in Southern Brazil - WOLFF,VERA R.S. (2018)
Abstract Olive production (Olea europaea L.) is a recent activity in Brazil and studies on the adaptability of olive trees varieties in the States are required. One of the problems that can hamper the development of olive trees is the incidence of pests, such as scale insects (Hemiptera, Coccomorpha). In this study, the associated scale insect species were found in ten varieties in an olive grove located at the Research Center of the Serra do Sudeste Region (30º33’15”S, 52º23’45”W) in Brazil. The surveys were carried out twice in each season (2013-2014). Six species of armored scale insect (Diaspididae) and two soft scales (Coccidae) were determined. Saissetia oleae (Coccidae) with 88.15% and Aspidiotus nerii (Diaspididae) with 5.85% occurred in all varieties of olive trees. The varieties Arbequina, Frantoio and Cipressino were with greater richness of scale insects, the highest values of diversity occurred in Frantoio, Arbequina and Picual; in Alfafara, Arbosana and Coratina there was a high dominance of one species (S. oleae).